MRGPRX2 and Adverse Drug Reactions - McNeil, Benjamin D. (Frontiers in Immunology, 2021)
Many adverse reactions to therapeutic drugs appear to be allergic in nature, and are thought to be triggered by patient-specific Immunoglobulin E (IgE) antibodies that recognize the drug molecules and form complexes with them that activate mast cells. However, in recent years another mechanism has been proposed, in which some drugs closely associated with allergic-type events can bypass the antibody-mediated pathway and trigger mast cell degranulation directly by activating a mast cell-specific receptor called Mas-related G protein-coupled receptor X2 (MRGPRX2). This would result in symptoms similar to IgE-mediated events, but would not require immune priming. This review will cover the frequency, severity, and dose-responsiveness of allergic-type events for several drugs shown to have MRGPRX2 agonist activity. Surprisingly, the analysis shows that mild-to-moderate events are far more common than currently appreciated. A comparison with plasma drug levels suggests that MRGPRX2 mediates many of these mild-to-moderate events. For some of these drugs, then, MRGPRX2 activation may be considered a regular and predictable feature after administration of high doses.